Plan-Draw-Evaluate (PDE) pattern in students' collaborative drawing: Interaction between visual and verbal modes of representation - Park, Joonhyeong; Tang, Kok-Sing; Chang, Jina (WILEY, 2021)
The use of group drawing to promote student-generated representation is a common instructional strategy as it combines the benefits of using visual representation and collaborative talk. Although the affordances of group drawing have increasingly been emphasized in science education, few studies have investigated how drawing as a visual mode interacts with group discourse as a verbal mode as well as how that interaction facilitates the development of students' collective ideas. Informed by theories in classroom discourse and multimodality, this paper examines the interaction process between a verbal and visual mode of representation as groups of students engaged in collaborative drawing during guided science inquiry lessons. On the basis of the analysis of data from a science class that adopted group drawing, we found and documented a recurring pattern, Plan-Draw-Evaluate or PDE pattern, in how the interaction between the verbal and visual modes occurred during collaborative drawing. This PDE pattern consisted of a triad of moves that alternate between the two modes and fulfilled various discursive purposes, such as suggesting, requesting, recording, visualizing, elaborating, agreeing, and rejecting. The PDE pattern provided a basic social structure that facilitated the collaboration and progression of students' ideas. With illustrations of PDE patterns and its variations, we argue that the PDE pattern provides an insight into the dynamic organization of interactions involved in group drawing that takes into consideration the multimodal affordances of verbal and visual modes of representation and the progression of ideas developed through collaborative discourse.